An Ethnobotanical Assessment of the Flora in Rampur Forest Division, Shimla District, Himachal Pradesh: Traditional Uses, Threats, and Manage ment Strategies (Prakriti - The International Multidisciplinary Research Journal, 2025)
This study focuses on the documentation and identification of the flora in the Rampur  forest division of Shimla district, Himachal Pradesh, highlighting its ethnobotanical  uses, traditional knowledge, cultural significance, prevailing threats and ongoing  conservation efforts. Local floral diversity serve multiple uses, primarily medicinal, but  their traditional uses also extend to food, fodder, fuel, and various cultural practices,  often intertwined with magico-religious beliefs that that help in conservation. This  heritage, however, is under severe threat from habitat degradation, over-exploitation,  climate change, developmental projects, and the erosion of traditional knowledge due  to modernization and diminishing intergenerational transfer. The study highlights  the urgent need of the community engagement and various conservation strategies to  safeguard both the flora and valuable indigenous knowledge systems. In the present  study, 42 plant species ethnomedicinal plants belonging to 32 families and 40 plant  species of other ethnobotanical uses belonging to 23 families were documented. All  the 82 plants are arranged in alphabetical manner with botanical names, local names,  family and their ethno botanical uses are documented in two tables.
Keywords: Ethnobotany; Traditional Knowledge; Biodiver sity Conservation; Community Engagement